High-resistance interval training improves 40-km time-trial performance in competitive cyclists - Taylor-Mason, A. M. (Sportscience, 2005)
Interval training at race-specific high cadences improves endurance cycling performance, but there is evidence that adding resistance to reduce the ca-dence might be more effective. AIM: To determine the effect of high-resistance interval training on endurance performance of male cyclists during the competi-tion phase of a season. METHODS: In a randomized controlled trial, 10 cyclists in a control group maintained usual training and competing while 12 cyclists in an experimental group replaced part of their usual training with high resistance interval training twice weekly for 8 wk. Mean power in a 40-km simulated time trial, maximal oxygen consumption (VO2max), incremental peak power, body composition, and leg strength were measured before and after training. RESULTS: Relative to control training, there were clear beneficial effects of resistance training on 40-km mean power (7.6%, 90% confidence limits ±5.0%). There were also clear beneficial effects on incremental peak power (3.5%, ±4.2%), VO2max in ml/minkg (6.6%, ±7.0%), and sum of 8 skinfolds (-12%, ±11%). Effects on body mass (-1.6%, ±1.9%) and thigh mus-cle area (0.6%, ±2.7%) were possibly trivial. Effects on VO2max in L/min and three measures of isokinetic leg strength were unclear, owing to large errors of measurement. CONCLUSIONS: High-resistance interval training produces a major enhancement in endurance power of athletes in the competitive season. The benefits of this form of training should transfer to competitive performance.